Low-temperature synthesis of single-phase Co7Sb2O12 - Brito, MSL; Escote, M. T.; Santos, COP; Lisboa Filho, Paulo Noronha [UNESP]; Leite, E. R.; Oliveira, JBL; Gama, L.; Longo, Elson [UNESP] (Elsevier B.V., 2004)
Polycrystalline Co7Sb2O12 compounds have been synthesized by a chemical route, which is based on a modified polymeric precursor method. In order to study the physical properties of the samples, X-ray diffraction (XRD), thermal analyses (TG and DSC), infrared spectroscopy (IR), specific surface area (BET), and magnetization measurements were performed on these materials. Characterization through XRD revealed that the samples are single-phase after a heat-treatment at 1100degreesC for 2h, while the X-ray patterns of the samples heat-treated at lower temperatures revealed the presence of additional Bragg reflections belonging to the Co6Sb2O6 phase. These data were analyzed by means of Rietveld refinement and further analyze showed that Co7Sb2O12 displays an inverse spinel crystalline structure. In this structure, the Co2+ ions occupy the eight tetrahedral positions, and the sixteen octahedral positions are randomly occupied by the Sb5+ and Co2+ ions. IR studies disclosed two strong absorption bands, v(1) and v(2), in the expected spectral range for a spinel-type binary oxide with space group Fd3m. Exploratory studies concerning the magnetic properties indicated that this sample presents a spin-glass transition at T-f similar to 64 K. (C) 2004 Elsevier B.V. All rights reserved.
Keywords: polymeric precursor method; spinet structure; Rietveld refinement; spin-glass behavior